Extraction and purification of cytotoxic compounds from Premna Serratifolia L. (Bebuas) for human breast cancer treatment - Salih, Ghassan Ali (Kulliyyah of Engineering, Internationai Islamic University Malaysia, 2015)
Cancer is one of the most lethal diseases all over the world, and breast cancer comprises 22.9 percent of all cancers excluding non-melanoma skin cancer. In the last two decades, all efforts have been focusing on the natural products to develop cheap, effective and safe anti-cancer drugs. Premna serratifolia is widely spread in tropical countries with many medicinal properties such as anti-oxidant and anti-inflammation. The present study aims to purify and identify cytotoxic compounds from P. serratifolia against MCF-7 cell line (human breast adenocarcinoma). Firstly the crude extract was evaluated and studied under four different solvents. The process of sonication extraction method to extract P. serratifolia leaves was optimized by Response Surface Methodology for two important parameters namely time and temperature for two responses that were yield of extract and antiproliferation activity (IC50) value. 11 experiments were designed and studied under different extraction condition. Crude extract from methanol and hexane demonstrated a significant activity against MCF-7 cell line with IC50 value of 58.40 µg/ml and 53.81 µg/ml, respectively. Extraction time has a great effect on the yield (p<0.05) while both time and temperature showed a significant influence (p<0.05) on the IC50 value. From the generated second order polynomial equation and validation experiment, the best sonication processing conditions for both extraction yield and anticancer activity at 30oC and 67 minutes. The methanolic crude extract was purified by using open column chromatography. Two isolated compounds showed a significant activity against MCF-7 cell line with IC50 value of 2.99 µg/ml and 1.54 µg/ml. NMR technique was applied to identify both compounds, 13CNMR and 1HNMR data was analysed and the compounds were proposed as (Apigenin-4'-methyl ether) and (5-Hydroxy-4'-methoxyflavone with sugar compounds) respectively. Another NMR spectrum which is HMBC NMR is required to confirm and finalize the final structures of both compounds.